2015
DOI: 10.1021/acs.orglett.5b01252
|View full text |Cite
|
Sign up to set email alerts
|

Oxalyl Chloride as a Practical Carbon Monoxide Source for Carbonylation Reactions

Abstract: A method for generation of high-quality carbon monoxide by decomposition of oxalyl chloride in an aqueous hydroxide solution is described. The usefulness of the method is demonstrated in the synthesis of heterocycles and for hydroxy-, alkoxy-, amino-, and reductive carbonylation reactions, in several cases under milder conditions than previously reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(42 citation statements)
references
References 43 publications
1
41
0
Order By: Relevance
“…Because the handling of pressurized CO is associated with safety issues, this strategy was not further evaluated. Hansen et al recently reported a convenient method based on the use of oxalyl chloride as a source of CO, [38] and so a one-pot reaction employing CO at balloon pressure was examined (Entry 3, 21 %). We speculated that the formation of acyl-sulfinamides, in this less pressurized reaction, would benefit from a stronger base.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the handling of pressurized CO is associated with safety issues, this strategy was not further evaluated. Hansen et al recently reported a convenient method based on the use of oxalyl chloride as a source of CO, [38] and so a one-pot reaction employing CO at balloon pressure was examined (Entry 3, 21 %). We speculated that the formation of acyl-sulfinamides, in this less pressurized reaction, would benefit from a stronger base.…”
Section: Resultsmentioning
confidence: 99%
“…Please note that products 2 can slowly decompose upon storage at room temperature. General Procedure for Coupling of Sulfinamide and Aryl Iodide Under CO Balloon Pressure: The preparation of CO (0.4 mL of oxalyl chloride) was as described by Hansen et al [38] The appropriate sulfinamide (0.354 mmol, 1.0 equiv. ), the appropriate aryl iodide (0.885 mmol, 2.5 equiv.…”
Section: General Procedures For Coupling Of Sulfinamides and Aryl Iodimentioning
confidence: 99%
“…The CO sources such as metal carbonyls, acid chlorides, silacarboxylic acids, chloroform, carbomylsilanes, formamides and formates have been extensively used for the aminocarbonylation reactions under transition‐metal‐catalyzed conditions. The CO generation from most of these sources requires strong bases, catalyst and activators . In addition, the development of catalytic carbonylation reactions for the synthesis of biologically active heterocyclic scaffolds has emerged as an efficient protocol in recent decades .…”
Section: Figurementioning
confidence: 99%
“…Therefore, the development of al-ternative safer sources of CO would be preferential for carbonylationr eactions. [3b] The CO sources such as metal carbonyls, [4] acid chlorides, [5] silacarboxylic acids, [6] chloroform, [7] carbomylsilanes, [8] formamides [9] and formates [10] have been extensively used for the aminocarbonylation reactions under transitionmetal-catalyzed conditions. The CO generation from most of these sourcesr equires strongb ases,c atalysta nd activators.…”
mentioning
confidence: 99%
“…In addition, Pd‐catalyzed decomposition of 9‐methylfluorene‐9‐carbonyl chloride (COgen) and fluoride‐mediated CO release from silacarboxylic acid enable the use of substoichiometric amounts of CO as well as the possibility to isotopically label the carbonyl carbon. Furthermore, base‐mediated decomposition of oxalyl chloride and chloroform have been reported as effective CO‐generating strategies for carbonylation chemistry. Notably, the latter facilitates the preparation of 13 C‐ and 14 C‐labeled carbonyl derivatives.…”
Section: Introductionmentioning
confidence: 99%